The New European Security Architecture: Publics Assess the Building Blocks of European Security. - United States Information Agency. Office of Research and Media Reaction. (Tufts University. Tisch Library., 2019)
How are publics likely to respond to the Clinton administration's vision for a new European security architecture? We examined this question from the perspective of west Europeans, central and east Europeans, Russians and Americans.